EFEKTIVITAS JERUK NIPIS DALAM MENURUNKAN BAKTERI SALMONELLA DAN ESCHERICHIA COLI PADA DADA KARKAS AYAM BROILER - Agustinus Hantoro Djoko Rahardjo (Universitas Padjadjaran, 2012)
The research objectives to study the effectiveness of lime juice as a decontaminant agent in reducing Salmonella and Escherichia coli bacteria in broiler carcasses breast sold at traditional markets. Decontamination of broiler carcasses breast through in immersion at the distilled water containing lime juice 5, 10, and 15% for 5 and 10 minutes. Results indicated thatdecontamination of lime juice with different concentrations after 5 and 10 minutes immersion has significant effect (P <0.05)reduce of Salmonella bacteria up to 96.43 percent. Decontamination are also able to reduce the number of bacteria Escherichia coli up to 57.38 percent, but is no difference in effect between concentration and long immersion of the number of bacteria on broiler carcass breast. The conclusion of this study is lime juice as an effective decontaminant agent to reduce of Salmonella and Escherichia coli bacteria as a whole broiler carcass breast.